Epitype designation for the name Biscutella didyma L. (Brassicaceae) - Vicente, Alicia; Alonso, Mª Angeles; Crespo, Manuel B. (Phytotaxa, 2015)
The Linnaean name Biscutella didyma was lectotypified in 1964 by a specimen consisting of an incomplete fruiting stem of a plant lacking well developed leaves. This species name, together with its lectotype, was proposed as conserved type for the genus. The taxonomic identity of the lectotype is here shown to be demonstrably ambiguous in the context of B. sect. Biscutella (B. ser. Lyratae), and might be related to either B. didyma var. didyma or B. didyma var. ciliata (B. didyma subsp. apula). Therefore, in the case that infraspecific taxa are accepted within B. didyma, an epitype is designated to warrant further application of the latter name in the sense it is been used in the last decades.